Identification of giant softshell turtle species (Reptilia: Testudines: Trionychidae: Pelochelys, Rafetus) in Vietnam - Truong, Nguyen Quang; Sang, Nguyen Van; Ngat, Le Nguyen; Kien, Tran (Academia Journal of Biology, 2014)
The allocation of two giant softshell turtle species of the genus Pelochelys and Rafetus is reviewed and confirmed based on morphological features of skulls and carapace bones of giant sofshell turtles collected in North Vietnam. The examination results of these specimens are also compared with description of foreign authors in international herpetological journals. At present, two species of giant softshell turtles were recorded in Vietnam including Pelochelys cantorii Gray, 1864 and Rafetus swinhoei (Gray, 1873). The current status of giant softshell turtle species is considered to be facing an extremely high risk of extinction in the wild. Therefore, according to the IUCN Red List categories and criteria (2001), both species of giant softshell turtles are proposed to re-evaluate in new version of Red Data Book of Vietnam.